Treasure Trove - "Smith, Dick King" (Puffen books: London, 1996)
Ben likes to collect money, and one day he finds a bag of gold coins under the floorboards outside his bedroom. His initial disappointment on being told that he must hand them in is only short-lived, as his friend finds a way for him to keep them
Keywords: Treasure troves